Ending violence against Indigenous peoples in Canada: a healthcare responsibility - Jessica Kolopenuk (The Lancet Regional Health. Americas, 2024)
Summary: By foregrounding the embodiment of colonial dispossession–how the body feels colonialism–this article theorises violence against Indigenous peoples in Canada, positioning it firmly within the purview of healthcare. The article critically questions the discourse of reconciliation currently shaping Indigenisation policies and Indigenous health research in the country’s public institutions. It contends that a narrow application of “closing the Indigenous health gap,” described more robustly by the Truth and Reconciliation Commission of Canada, falls short of addressing the root problem: “ending colonial violence.” Aligning with critical Indigenous studies scholarship, I redirect representations of Indigenous health away from the presumption of deficit. I argue that health care in Canada is responsible for recognising and confronting colonial violence as a matter of public health. As a starting point, this responsibility involves implementing the relevant Calls for Justice outlined in Reclaiming Power and Place: The Final Report of the National Inquiry into Missing and Murdered Indigenous Women and Girls.